LEGAL PROTECTION FOR MICRO, SMALL, MEDIUM, CULINARY BUSINESS ACTORS THE IMPACT OF FOOD REVIEWS BY FOOD VLOGGERS FROM IMAM IBNU QUDAMAH'S PERSPECTIVE - Salsabila Alamanda; Sugeng Wanto (Program Pascasarjana UIN Sumatera Utara, 2025)
The advancement of social media has introduced a new phenomenon in the culinary world: the emergence of food vloggers whose reviews can influence the image, reputation, and even the sustainability of micro, small, and medium-sized enterprises (MSMEs). Positive reviews can boost popularity, sales, and consumer trust, while negative and unobjective reviews have the potential to cause economic losses and even business closures. This research aims to analyze the forms of legal protection for culinary MSME owners affected by food vlogger reviews and to examine the views of Imam Ibnu Qudamah from an Islamic legal perspective. The method used is empirical legal research with a sociological approach through interviews, field observations, as well as a review of literature and regulations, such as the ITE Law, Consumer Protection Law, and the Civil Code. The results show that legal protection can be pursued through litigation (civil and criminal) as well as non-litigation channels (mediation and clarification). Imam Ibnu Qudamah's perspective emphasizes the principles of honesty, the prohibition of tadlis (deception), and proper manners in delivering criticism so that it does not fall into the categories of ghibah (backbiting) or slander. Case studies on Angkringan P2K and BURNI Coffee demonstrate that while food vlogger reviews bring great promotional opportunities, the risks of excessive expectations and negative reputation are also unavoidable. Therefore, food vloggers are required to be ethical, honest, and objective, while MSME owners need to maintain quality and understand the mechanisms of legal protection. These findings underscore the importance of balancing freedom of expression on social media with the protection of MSME rights to create a fair and sustainable culinary ecosystem.